Leukocyte Adhesion Molecules in Diabetic Retinopathy - Kousuke Noda; Shintaro Nakao; Susumu Ishida; Tatsuro Ishibashi (Journal of Ophthalmology)
Diabetes is a systemic disease that causes a number of metabolic and physiologic abnormalities. One of the major microvascular complications of diabetes is diabetic retinopathy (DR), a leading cause of blindness in people over age 50. The mechanisms underlying the development of DR are not fully understood; however, extensive studies have recently implicated chronic, low-grade inflammation in the pathophysiology of DR. During inflammation leukocytes undergo sequential adhesive interactions with endothelial cells to migrate into the inflamed tissues, a process known as the “leukocyte recruitment cascade” which is orchestrated by precise adhesion molecule expression on the cell surface of leukocytes and the endothelium. This paper summarizes the recent clinical and preclinical works on the roles of leukocyte adhesion molecules in DR.